Analisa Faktor Eksternal dan Perencanaan Pemasaran PT Nuno Care Post Partum Depression Pusat Perawatan Pasca Melahirkan - Hariani Widyastuti; Dimas Angga Negoro; Unggul Kustiawan; Mohamad Reza Hilmy (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Globally, 1 in 8 mothers experience postpartum depression (PPD). In Indonesia, many postpartum mothers face various psychological conditions, such as postpartum stress, extreme fatigue, emotional disturbances, severe anxiety, loss of bonding with their baby, and changes in their lifestyle. This study aims to analyze in depth the external factors that influence the marketing planning of PT Nuno Care, a postpartum care center that focuses on postpartum depression management. A qualitative descriptive approach is used to understand the conditions and dynamics of the external environment that influence the company's marketing strategy. Data were collected through literature studies, interviews with management, and market observations aimed at capturing various aspects such as market conditions, industry competition, government regulations, and technological advances that continue to develop. This study emphasizes the importance of adaptation and responsiveness to changes in the external environment so that marketing strategies can be aligned with market needs and preferences. The results of the study indicate that marketing success is highly dependent on the company's ability to anticipate and utilize opportunities and overcome external threats. The recommendations provided aim to assist management in formulating and implementing effective, innovative, and sustainable marketing strategies to enhance competitiveness and support PT Nuno Care's long-term growth. Marketing strategies should be directed at increasing brand awareness regarding the importance of postpartum care services, optimizing digital marketing targeting new mothers and families as decision-makers, and strengthening partnerships with hospitals, maternity clinics, and healthcare professionals as primary referral sources.